Stable Allocations of Risk - Péter Csóka; Jean-Jacques Herings; László Á. Kóczy (Hungarian Academy of Sciences, Institute of Economics, 2007)
Measuring risk can be axiomatized by the concept of coherent measures of risk. A risk environment specifies some individual portfolios' realization vectors and a coherent measure of risk. We consider sharing the risk of the aggregate portfolio by studying transferable utility cooperative games: risk allocation games. We show that the class of risk allocation games coincides with the class of totally balanced games. As a limit case the aggregate portfolio can have the same payoff in all states of nature. We prove that the class of risk allocation games with no aggregate uncertainty coincides with the class of exact games.
Keywords: C71; 330; Coherent Measures of Risk; Risk Allocation Games; Totally Balanced Games; Exact Games; Risiko; Messung; Spieltheorie; Transferierbarer Nutzen; Theorie